A facile "bottom-up" approach to prepare free-standing nano-films based on manganese coordination clusters - VENKATESAN, MUNUSWAMY (My University, 2013)
We present herein a novel method to prepare free-standing Dried Foam Films (DFFs) whereby individual polynuclear manganese complexes cover quantitatively the holes of micro-grids; the fabricated, homogeneous films have a cross-sectional thickness of only ca. 5 nm and are characterised by high mechanical stability.
PUBLISHED
Keywords: Dried Foam Films (DFFs); Dried Foam Films (DFFs)